Structural behaviour of post-tensioned precast concrete sub-structures under an edge column removal scenario - Tran, Manh Ha (2024)
In this study, three one-quarter scaled-down specimens were tested under quasi-static loading focusing on an edge column loss scenario. They included two 2D beam-column sub-assemblages and one 3D beam-slab sub-structure. One of the two 2D sub-assemblages was attached with a one-sided wing slab to simulate L-shape effect from the slab supported on a perimeter beam. All the specimens used precast technique with wet-connection joints and semi-precast slabs; only the primary beams had post-tensioned (PT) tendons. The test results could be used to quantify load-resisting mechanisms at different stages, as well as respective contributions of the primary beams, secondary beams and slabs. Moreover, the influence of PT tendon on load-resisting mechanisms and failure modes was thoroughly discussed. In addition, a simplified analytical method was proposed to predict yield resistance capacity of a post-tensioned precast concrete (PTPC) sub-structure under an edge column removal scenario. This method serves as a practical tool for preliminary design purposes, facilitating structural engineers to quickly calculate structural capacity and obtain the individual contributions of structural members.